An application phase-modular rectifier applied to MMC with medium voltage based on wind turbine generator - Watanakul, Narin (International Journal of Engineering and Technology, 2014)
This paper proposes two stages of controller. First stage, direct power control (P-Q control) applied single-phase structure of multilevel modular converter (MMC) , multilevel cascaded H-Bridge inverter with 9-level SPWM injection to medium voltage (24kV) based on wind turbine generator (PMSG)rated capacity 25kVA. Second stage, three-phase PFC rectifier with phase-modular Y-rectifier, boost–type. The separate dc sources (DC-links) average voltage at 178V (Vdc1-Vdc12). This study is concerned with the application, operating, principle, and design example. The unity power factor operation of PMSG is realized by controlling of phase-modular Y-Rectifier system, and the current waveform distortion results increase of the lower harmonics distortion. The P-Q controller can make it possible of the grid line current phase by providing the direct instantaneous power control in the steady state under the active power and reactive power command. The data collected by PSIM and MATLAB simulation are used in comparison with the experimental tester of results. This provides guideline to further analyze and improvement energy efficiency and power quality in electrical system pertinent to wind turbine generator (PMSG). Keywords: Wind Turbine Generator, Permanent Magnet Synchronous Generator (PMSG), Phase-Modular Y-Rectifier, Cascaded H-Bridges, Modular Multilevel Converter (MMC), Power Quality, Unity Power Factor, Harmonics.